Sucrose fatty acid esters: synthesis, emulsifying capacities, biological activities and structure-property profiles. Issue 19 (28th October 2021) - Teng, Yinglai; Stewart, Scott G.; Hai, Yao-Wen; Li, Xuan; Banwell, Martin G.; Lan, Ping
Abstract: The notable physical and chemical properties of sucrose fatty acid esters have prompted their use in the chemical industry, especially as surfactants, since 1939. Recently, their now well-recognized value as nutraceuticals and as additives in cosmetics has significantly increased demand for ready access to them. As such a review of current methods for the preparation of sucrose fatty acid esters by both chemical and enzymatic means is warranted and is presented here together with an account of the historical development of these compounds as surfactants (emulsifiers). The somewhat belated recognition of the antimicrobial, anticancer and insecticidal activities of sucrose esters is also discussed along with a commentary on their structure-property profiles.